Sustainable Behavior Change for Health Supported by Person-Tailored, Adaptive, Risk-Aware Digital Coaching in a Social Context: Study Protocol for the STAR-C Research Programme - Ng, Nawi; Eriksson, Malin; Guerrero, Esteban; Gustafsson, Carina; Kinsman, John; Lindberg, Jens; Lindgren, Helena; Lindvall, Kristina; Lundgren, Anna Sofia; Lönnberg, Göran; Sahlen, Klas-Göran; Santosa, Ailiana; et al. (Frontiers in Public Health, 2021)
Introduction: The Västerbotten Intervention Programme (VIP) in the Region Västerbotten Sweden is one of the very few cardiovascular disease (CVD) prevention programmes globally that is integrated into routine primary health care. The VIP has been shown as a cost-effective intervention to significantly reduce CVD mortality. However, little is known about the effectiveness of a digital solution to tailor risk communication strategies for supporting behavioral change. STAR-C aims to develop and evaluate a technical platform for personalized digital coaching that will support behavioral change aimed at preventing CVD. Methods: STAR-C employs a mixed-methods design in seven multidisciplinary projects, which runs in two phases during 2019–2024: (i) a formative intervention design and development phase, and (ii) an intervention implementation and evaluation phase. In the 1st phase, STAR-C will model the trajectories of health behaviors and their impact on CVDs (Project 1), evaluate the role of the social environment and social networks on behavioral change (Project 2) and assess whether and how social media facilitates the spread of health information beyond targeted individuals and stimulates public engagement in health promotion (Project 3). The findings will be utilized in carrying out the iterative, user-centered design, and development of a person-tailored digital coaching platform (Project 4). In the 2nd phase, STAR-C will evaluate the implementation of the coaching programme and its effectiveness for promoting behavioral change and the spreading of health information across social networks and via social media (Project 5). The cost-effectiveness (Project 6) and ethical issues (Project 7) related to the coaching programme intervention will be evaluated. Discussion: The STAR-C research programme will address the knowledge and practice research gaps in the use of information technologies in health promotion and non-communicable disease (NCD) prevention programmes in order to narrow the health inequality gaps. Ethics: STAR-C has received approval from the Swedish Ethical Review Authority (Dnr. 2019-02924;2020-02985). Dissemination: The collaboration between Umeå University and Region Västerbotten will ensure the feasibility of STAR-C in the service delivery context. Results will be communicated with decision-makers at different levels of society, stakeholders from other regions and healthcare professional organizations, and through NGOs, local and social media platforms.